The Meaning of Political Messages in Carousel Posts on @ganjar_pranowo’s Instagram Account during the 2024 Electoral Campaign Period - Sentanu Chandra; Ido Hadi; Agusly Irawan Aritonang (Petra Christian University, 2024)
This research is motivated by the phenomenon of the 2024 elections, focusing on the digital political campaigns based on social media. The study focused on examining the meanings of political messages constructed by the 2024 presidential candidate, Ganjar Pranowo, by relating them to the philosophy of Javanese cultural leadership. This is due to the contrast between the results of the party’s legislative elections and its vote acquisition in the presidential election contest. The type of research used is descriptive qualitative with the semiotic analysis method of Roland Barthes. The research subject consists of carousel posts on the Instagram account @ganjar_pranowo, while the research object is the meaning of Political Messages. The study found that the meaning of political messages is derived from the visible verbal and non-verbal messages. It also discovered the correlation between the meanings of ‘Penguin’ and ‘Swastika’ which were capitalized as campaign messages. Furthermore, the researcher interprets the message meanings as Javanese-centric leadership in Indonesia presidential, redefinition of the meaning ‘Merakyat’, the paternalistic side in ‘wong cilik’ politics, and the implementation of Hastabrata philosophy rooted in Ganjar Pranowo.